WANITA DALAM PENDIDIKAN ISLAM KLASIK - Sihaloho, Wardani (Jurnal Ushuluddin, 2023)
In Islam, women are required to seek knowledge just like men. Islam has equated women and men in matters of spirituality and religious obligations without any differences in the fields of knowledge and education. The Messenger of Allah SAW said which means: "Hisham bin Ammar Hafs bin Sulaiman Kasir bin Sanjir said to us from Muhammad bin Sirin from Annas bin Malik who said, the Messenger of Allah SAW said, "Seeking knowledge is obligatory for every Muslim (male and female)". In the Jahiliyah society in the Arab lands, women had the right to study and among these women were famous writers and poets (such as Shifa' al-Adawiyah, who was very good at reading and writing in the Jahiliyah era before the advent of Islam). After the advent of Islam, the life of the mind began to become more active and developed among the Arab people, women also obtained social rights that they had never had before the advent of Islam.  therefore education developed among women. What is intended to be expressed in this article is how women's education actually was in classical Islamic civilization: opportunities, tendencies, and the relationship between provisions contained in normative doctrine and historical reality.